The Implementation Of Verbal Learning Soccer Strategy To Improve Students’ Achievement In Sport Education At The Fifth Grade Students Of Sd Negeri 12 Maredan Barat In Academic Year 2015/ 2016 - Erniati Erniati (Jurnal Ilmiah Pendidikan Scholastic, 2018)
Natural science is closely related to everyday human life, for example, familiar with various energy sources that are often encountered in everyday life and usefulness. A teacher should be able to use strategies that can create conditions and learning situations that enable students to actively shape, discover and develop their knowledge. One of the innovations teachers can make is to use student-centered strategies. A student-centered strategy means that every learning activity can provide the widest possible opportunity for students to be directly involved in the learning process. Based on the background and the above symptoms, it can be formulated the problem in this research as follows: "whether the implementation of verbal football learning strategy can improve student learning outcomes on the sport subject in class V in SD Negeri 12 Maredan Barat?" The subjects in this study were teachers and students of class V which numbered 28 people in SD Negeri 12 Maredan Barat. While the object of this research is the application of football verbal strategies to improve student learning outcomes in physical education subjects in class V SD negeri 12 Maredan Barat. This study consisted of two variables, the variables X and Y. As the variable X variable is football verbal learning strategies, while as its Y variable is the result of studying physical education with competency standards to understand how green plants make food.This classroom action research site was conducted at SD Negeri Maredan Barat.The research time has been conducted starting from September to October 2015.This research is a classroom action research (PTK).Classroom action research is a reflective form of research by taking certain actions to improve and improve classroom teaching practices professionally.Classroom action research seeks to improve and develop the professionalism of teachers in fulfilling their duties. Students' learning outcomes during the learning process before the action was obtained averaged 63.33 were at intervals of less than 65 with the category "Less". Meanwhile, after the corrective action with verbal soccer strategy in cycle I, student learning outcomes occur with an average increase of 70.83 at intervals 65-70 with the category "Enough". While the action on the second cycle also increased with an average of 74.58 are at intervals 71-84 with the category of "Good"